Assessment of serum ferritin and thyroid hormones level in acute ischemic stroke and their association with hemorrhagic conversion - Giri, Richa; Ahamed, Faim; Agarwal, Saurabh; Kumar, Lalit (International Journal of Advances in Medicine, 2021)
Background: Acute ischemic stroke is a significant cause of mortality and the leading cause of long-term disability in the United States. Collective evidence suggests that low T3 levels and serum ferritin levels instantly following acute ischemic stroke are connected with greater stroke sternness, higher death rates, and poor functional outcomes. The aim of the study was to assess the serum ferritin and thyroid hormones level in acute ischemic stroke their association with hemorrhagic conversion. Methods: In this observational study, 60 acute ischemic stroke patients aged ≥ 18 years of both gender who were reported with focal neurological deficit lasting greater than 24 hours were included. Clinical severity of stroke was assessed at admission and on the 7th day using Glasgow coma scale (G.C.S.), serum ferritin level, and thyroid hormones level were measured at admission and on the 7th day in all these subjects. Results: Overall mean age of patients was 56.28±11.45 years with a range of 29-87 years; 61.7% were male patients. Ischemic stroke was found in 55 (91.7%) patients, while 5 (8.3%) patients showed hemorrhagic conversion. Serum Ferritin and T3 level shows a significant association with G.C.S. score (p<0.05). Hemorrhagic Conversion patients were significantly greater in-hospital stay than the acute ischemic stroke group (p<0.05). Conclusions: In our study, it was observed that after acute ischemic stroke high ferritin level and low T3 is associated with worse neurological outcome and linked to the poorer results at hospital discharge.